2018
DOI: 10.1515/reveh-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide management approach towards protecting the safety and health of farmers in Southeast Asia

Abstract: Abstract Background: It is estimated that pesticide production and use have increased continuously in the countries of Southeast Asia in recent years. Within the context of protecting the safety and health of workers in the agricultural sector, there is an existing gap in the implementation of the pesticide management framework because safety and health effects arising from occupational exposures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
2
12
0
2
Order By: Relevance
“…were also reported. The inhibited AChE and BChE activity associated with cholinergic dysfunctions including adverse neurobehavioral outcomes in pesticide‐exposed workers has been determined in some studies . In the present study, the activity of AChE is found to be significantly decreased in pesticide‐exposed agriculture workers consistent with the previous findings …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…were also reported. The inhibited AChE and BChE activity associated with cholinergic dysfunctions including adverse neurobehavioral outcomes in pesticide‐exposed workers has been determined in some studies . In the present study, the activity of AChE is found to be significantly decreased in pesticide‐exposed agriculture workers consistent with the previous findings …”
Section: Discussionsupporting
confidence: 91%
“…Limited number of studies were available to report the pesticide‐induced free radical generation associated with toxicity and other neurobehavioral dysfunctions such as dyslipidemia, hypertension and sleep apnea transformed into neurodegenerative and neurobehavioral outcomes including Parkinson's and Alzheimer's disease in agriculture workers . An increase in the level of lipid peroxidation and decrease in the activity of catalase, GSH and SOD in pesticide‐exposed agriculture workers as observed in the present study suggesting the increased oxidative stress due to pesticide toxicity in exposed agriculture workers and the findings are consistent with the earlier studies .…”
Section: Discussionsupporting
confidence: 90%
“…It has been estimated that the volume of pesticides used in SE Asian countries increased by approximately 400 per cent in the first decade of the new millennium [ 3 ]. Thailand is reported to be the highest user of imported pesticides by volume in the region [ 21 ], while Vietnam has the highest application rate of 16.5kg/hectare [ 22 ]. However, analysis by these latter authors shows that the acceleration in the use of pesticides has been higher in recent years in Cambodia and Lao PDR than in Vietnam and Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides compounds have been used widely in the agricultural sector to kill pests, weeds and increase harvests productivity (1)(2)(3)(4)(5). The use of pesticides is the basis of agriculture intensification developed in the middle of the 20 th century (6)(7) to improve the productivity and quality of farming commodities (4,(8)(9).…”
Section: Introductionmentioning
confidence: 99%